A Distributed Optimal Scheduling Method Based on Microgrid Cluster of Plug and Play. Issue 1 (March 2021) - Tang, W; Liu, Q; He, P; Liu, G F
Abstract: This paper proposes a distributed optimization method to solve the problems of centralized optimization and centralized management of a microgrid. Also, the distributed optimization solution method upgrade to a process of distributed iterative solution and optimization, which can solve the distributed optimization problem of a large microgrid cluster. According to iterative calculation, accord the augmented Lagrange function supports the centralized optimization problem divided into corresponding subproblems, and the penalty factors of interconnected variables considered to adjust the consumption of local resources, to make microgrid cluster (MGC) more flexible. In particular, the framework of multi-verse consistency and model predictive control (MPC) can help the global optimization reach the optimal quickly. In this paper, the simulation is solved by Gurobi commercial solver in MATLAB. The results show that the proposed method needs only a few iterations to achieve global optimization, and the effectiveness of plug and play proved.